The readiness of transit oriented development in Nusajaya, Johor [electronic resource] - Zulazhar Abd. Gahni @ Abd. Ghani, 1975- (2013)
Thesis (Sarjana Sains (Perancangan dan Pengangkutan)) - Universiti Teknologi Malaysia, 2013